Selection of Talented Young Players Through Volleyball Championship in The Village of Bulurejo in 2020 - Edi Irwanto; Bayu Septa Martaviano Triaiditya; Danang Ari Santoso (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2020)
The purpose of this service is to hold a volleyball match to get young volleyball players and form a volleyball team in the village of Bulurejo in preparation for the inter-village volleyball championship at Purwoharjo sub-district level. The method used is to monitor volleyball matches between hamlets in the village of Bulurejo. The results of this activity were the talented young players and the volleyball team from the village of Bulurejo. The best players have good abilities in terms of physical conditions and basic volleyball technical skills. Where these two factors are very closed related to the ability to play volleyball a player. Because to have good basic volleyball technical skills requires good physical condition.